Chronic unpredictable mild stress induced depression-like behaviours and glutamate-glutamine cycling dysfunctions in both blood and brain of mice - Ya-Ping Chen; Chuang Wang; Jiang-Ping Xu (Taylor & Francis Group, 2019)
Context: Currently, there is no cure or early preclinical diagnostic assay available for depression. Recently, depression has been observed in association with metabolic abnormalities of the glutamate (Glu)-glutamine (Gln) cycling, which is regulated by Glu, Gln and γ-aminobutyric acid (GABA) amino acids. Objective: The purpose of this study is to determine the changes of Glu, Gln and GABA in blood and brain of chronic unpredictable mild stress (CUMS) induced mice and to clarify the depression biomarkers in the Glu-Gln cycling. Materials and methods: Male Kunming mice were divided into model group and control group randomly (n = 12). The depression model of mice was established by CUMS stimulation for 56 days. The liquid chromatography-fluorescence method was used for simultaneous determination of Glu, Gln and GABA in the plasma and brain of mice. o-Phthalaldehyde and β-mercaptoethanol were used as pre-column derivatization reagents. Neurotransmitters were analysed on high performance liquid chromatography (HPLC) on an HPH C18 column in combination with a fluorescence detector. Results: The method was simple, highly sensitive and showed excellent linearity with regression coefficients higher than 0.999, good accuracy (95-108%) and good inter-day precision (RSD <15%) for all analytes. Limit of quantification (LOQ) values were established as 0.01, 0.01 and 0.005 μg/mL for Glu, Gln and GABA. The GABA in the CUMS mouse brain (p < 0.01) was significantly increased and Gln in plasma (p < 0.01) and brain (p < 0.01) were both decreased. Conclusions: Our study demonstrates that the Gln in plasma can be used as a biological marker of depression.